Socjologiczne problemy kształtowania aktywności innowacyjnej w przemysłowych zakładach pracy - Stankiewicz, Janina; Walkowiak, Jerzy (Wydział Prawa i Administracji UAM, 1984)
The article presents social substance of innovational system of decision and protection towards efficiency increasing movement containing all organizational units of various institutions, unions, societies, which activity is related to innovations. Basic functions of the system are characterised: 1) aiding and realization, 2) results and economy, 3) information- popularizing- training, 4) social integration, 5) protection and "securing", 6) stabilization and consolidation. It is indicated that enumerated functions of the system of decision and protection are realized by means of various strategies: 1) professional, oriented "towards plant" and accomplished by plant services, including units of rationalization and units of technology and developement; 2) oriented to plant, based on collaboration and cooperation of socio- professional inventive services with other units of plant; 3) professionalpro- plant combined with local stimulation; centrally controlled running almost exclusively according to normative, organizational and administrative directives coming from superior authorities. Various directions of activities of the discussed system are specified and characterized: 1) popularizing and information, 2) stimulation, 3) advising-aiding- -training, 4) assessing and decision, 5) substantial (promotion and dissemination). Some forms of stimulating innovational activity are described: 1) exchange, 2) thematical contests, 3) tournaments. Sociological typology of stimulating innovational activity and "administering" innovation in industrial plant is presented with due regard paid to previous conclusions, it contains following directions: 1) mobilisation, spontaneity, 2) directives, planning, 3) directives, arrangement 4) directing of a thematic feature, 5) socially obliging directions. The study indicates the types of systems, applied strategies, directions of activity and types of external stimulation which were prevalent in 1970 - 1980 in examined plants. It is also pointed which of those activities are more profitable for plant and which would fulfill needs and aspirations of workers.
Sociological aspects of forming innovational activity in industrial plants